Caesarean section and risks for mother - Janoušková, Kateřina; Vítková, Ludmila; Voříšková, Irena; Bubeníková, Štěpánka; Hrubá, Renata (Profese Online, 2019)
Introduction: Caesarean section is the most common obstetric operation that ends the delivery and pregnancy in the third trimester. It is the surgical procedure and like any other operation, it can pose risks to both, the mother and the newborn child. According to current studies, after the caesarean section is perfermed it is possible to observe a link between the operation and occurence of gynecological problems, complications in subsequent pregnancies, and dysfunction of mother´s pelvic floor. Aim: The main aim of this review was to present and summarize the published findings of the issue of caesarean section from the perspective of maternal risks. Methodology: Electronic information databases PubMed, EBSCO, Medvik (BMČ), and Google Scholar were used for searching literal sources. Documents from the period of 2007-2018 were searched using keywords verified in the Medical Subject Headings thesaurus and combined via using Booel´s operators. Results: In the perspective of short-term risks, planned CS is comparable with vaginal birth. However, acute SC is associated with a higher incidence of blood loss, visceral injury, infectious and thromboembolic complications. The long-term risks of CS consist of gynecological problems such as intermenstrual spotting, dysmenorrhoea, and pelipathy. CS also poses significant risks for next pregnancies. Conclusion: Many studies dealings with the risks of caesarean section show inconsistent results. In the context of the increasing number of caesarean sections, more detailed research is needed to clarify this area of interest. It should also be noted that caesarean section may pose risks not only to the mother but also to the newborn child.
Keywords: Caesarean section; uterine scar; subsequent pregnancy; pelvic floor dysfunction